Identification of Needs for Increasing the Selling Value of Salted Fish in Kali Baru - Christian, Michael; Japri, Evan Pratama; Rembulan, Glisina Dwinoor; Yulita, Henilia (Jurnal Pengabdian dan Kewirausahaan, 2022)
Salted fish is one important product resulting from the process of catching fish. It is mostly produced by residents who live close to the sea. Besides being sold in large quantities to collectors, salted fish can also be sold independently by salted fish producers. This activity aims to identify the needs of salted fish producers in Kali Baru, Cilincing, North Jakarta, for increasing the selling value of salted fish. This is important so that salted fish producers receive better compensation for the salted fish produced. A community service team from Universitas Bunda Mulia carried out field observations to identify needs of producer partners. The team observed that partners needed more “irik” bamboo mats, especially when fish arrive in large quantities, so that fish could be dried in one batch. Additionally, for the boiling process of small fish, partners need “laha” baskets to support the optimization of the process. To increase the selling value of salted fish, partners need educational counseling support for making labels and packaging for their products. They could also benefit from counseling on how to sell salted fish online, especially in an online marketplace. After identification of the needs of salted fish producer partners, continued community service is planned to address these needs.